Biogeography of Salak Pondoh Cultivation in Nganggring Tourism Village: Analysis of Geographic Distribution, Environmental Influences, and Conservation Sustainability - Ramadhani, Glora; Herdananta, Bisma Yoga; Kusuma, Alvina Novelinda; Mardiyanto, Muhammad Bondan; Wijayanti, Sovia (JURNAL ILMU-ILMU KEHUTANAN, 2024)
Nganggring Tourism Village, Sleman, Yogyakarta, as a location for Pondoh salak cultivation, is located in a mountainous area with annual rainfall of 2760 mm, an altitude of 708 meters above sea level, an average temperature of 26.1°C, and regosol soil type. Environmental analysis shows that Nganggring Tourism Village has ideal conditions for cultivating pondoh salak. The interaction of Pondoh salak plants with the local ecosystem involves a mutualistic relationship with protective plants, mycorrhizal fungi and pollinating insects. Even though it has a positive impact on biodiversity and soil fertility, Pondoh salak plants can also pose a risk of spreading pests and plant diseases. Therefore, this journal proposes a sustainable management strategy for pondoh salak cultivation through wise spatial zoning, use of green technology, diversification of the local economy, partnerships and social management. This strategy is expected to increase production, maintain the ecosystem and improve the welfare of farmers, thereby supporting the sustainability of pondoh salak cultivation in a broader socio-economic context.